2013
DOI: 10.1007/978-1-4471-5143-2_7
|View full text |Cite
|
Sign up to set email alerts
|

A Cumulative Belief Degree Approach for Prioritization of Energy Sources: Case of Turkey

Abstract: Energy planning is difficult to model owing to its complex structure, with numerous decision makers, criteria, and scenarios. Fortunately, decisionmaking methods can be helpful for the sustainable development of energy, by the evaluation of different energy sources with regard to multiple aspects, for example, economic, environmental, political etc. In this study, a methodology based on a cumulative belief degree approach is proposed for the prioritization of energy sources. The approach enables the use of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Environmental impact analysis environmental and ecological decision-making [84][85][86], life-cycle assessment [2, 87] C1.4. Energy evaluation and assessment investments [88][89][90][91], sustainability assessment of energy systems [38,[92][93][94][95], sources, technologies and options [12,13,15,28,35,39,94,[96][97][98], power expansion alternatives [99][100][101], plants [47,102], power generation scenarios [103,104] quantitative and qualitative factors. Based on [10], multi-attribute utility theory (MAUT), analytic hierarchy process (AHP), analytic network process (ANP), preference ranking organization method for enrichment evaluations (PROMETHEE), elimination and choice expressing reality (ELECTRE), and fuzzy models were the most commonly used techniques for renewable and sustainable energy planning.…”
Section: An Overview Of Reviews On Epdmmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental impact analysis environmental and ecological decision-making [84][85][86], life-cycle assessment [2, 87] C1.4. Energy evaluation and assessment investments [88][89][90][91], sustainability assessment of energy systems [38,[92][93][94][95], sources, technologies and options [12,13,15,28,35,39,94,[96][97][98], power expansion alternatives [99][100][101], plants [47,102], power generation scenarios [103,104] quantitative and qualitative factors. Based on [10], multi-attribute utility theory (MAUT), analytic hierarchy process (AHP), analytic network process (ANP), preference ranking organization method for enrichment evaluations (PROMETHEE), elimination and choice expressing reality (ELECTRE), and fuzzy models were the most commonly used techniques for renewable and sustainable energy planning.…”
Section: An Overview Of Reviews On Epdmmentioning
confidence: 99%
“…The involved stakeholders often express difficulties to provide precise assessments when evaluating alternatives according to criteria. This is further complicated in multiple stakeholders' environments due to the different levels of knowledge, resulting in biased decisions [4,15,35]. Fuzzy set theory was introduced by Zadeh in [36] as an effective instrument to facilitate decision-making situations in vague and ambiguous contexts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several experts were asked to assess different sources of energy with respect to the relevant criteria in Turkey. Based on the evaluation of the participants, the performance of "oil" option on the criterion "National economic benefits" can be modelled by the following distribution [10]:…”
Section: Problem Identification: Conventional Decision Matrix Vs Belmentioning
confidence: 99%
“…Kabak and Ruan showed that the risk can be dealt with a CBD approach that is appropriate for assessment of vague and linguistic‐based information. Similarly, Kabak et al . used it for identifying the risk levels for the energy policy evaluation problem in Turkey.…”
Section: Preliminariesmentioning
confidence: 99%
“…While Ruan et al . utilized an OWA operator‐based aggregation, Kabak et al . proposed to use the subjective weights determined by decision experts.…”
Section: Preliminariesmentioning
confidence: 99%